Temporal reflection of electromagnetic waves in simple polar-molecule reactions. Issue 6 (24th October 2019) - Liu, Xingpeng; Yan, Dandan; Huang, Kama
Abstract : Purpose: The purpose of this paper is to present the temporal reflection of electromagnetic waves (EMWs) in simple polar-molecule reactions whose polarization changes with the proceeding of the reactions. Design/methodology/approach: At a temporal boundary, based on the continuity of the electric displacement and magnetic induction, the reflected condition of EMWs is obtained, and the expression of the transmission and reflection coefficients in the reactions is derived. Subsequently, a one-dimensional model is used to validate the reflected condition and expression. Findings: If the time scale of the component concentration variation is greater than the wave period, the polarization of the reactions at a temporal boundary is continuous. The reflection does not happen. On the other hand, when the time scale of the component concentration variation is smaller than the wave period, the polarization is not continuous at a temporal boundary. The impedance of the reactions at the temporal boundary changes and the reflection occurs. Originality/value: The results may be helpful in disclosing the non-uniform distribution of EMWs in chemical reactions.